Introduction to Social Network Research: General Introduction and Major Terminology - Anil Kumar Chaudhary; Laura A. Warner (EDIS, 2015)
Social networks play an important role in the functioning of society and have an important effect on the actions of an individual or organization. It is very important for Extension educators to understand the networks of their clientele in order to perform better and develop more impactful Extension programming for their target audiences. This 5-page fact provides a brief description of network concepts and the terminology used in network studies, so that Extension educators may be more comfortable interpreting and using the results of SNA research to improve the efficiency and productivity of Extension organizations. Written by Anil Kumar Chaudhary and Laura A. Warner, and published by the UF Department of Agricultural Education and Communication, February 2015.